Coupled analysis of turbomachinery blades - Düz, Bülent. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Three-dimensional analysis of uid ow over turbomachinery blades and the deformation of the blades under aerodynamic loads are modeled and simulated using computational techniques. Decomposition into computational sub-domains and using multi-level partitioning hierarchy characterize the procedure of solving the non-linear set of governing partial di erential equations. Grid generation techniques and various formulations of Navier-Stokes equations are studied. These equations are linearized using Newton's method, and the resulting system of equations are solved using matrix- free implementations of the preconditioned Krylov techniques. Pressure values determined as a result of uid analysis are implemented as bound- ary conditions into ANSYS environment. Displacements are found after solid analysis performed by ANSYS and transferred into uid analysis to update the geometry. The computations were carried out for di erent Reynolds numbers and the results of the numerical simulations are discussed and compared.
Keywords: Turbomachines -- Fluid dynamics.